Discovery of a hyperalkaline liquid condensed phase: significance toward applications in carbon dioxide sequestration - Bewernitz, Mark A.; Schneider, Jacob; Camiré, Christopher L.; Kang, Seung-Hee; Bourcier, William L.; Wade, Richard; Constantz, Brent R. (Frontiers in Bioengineering and Biotechnology, 2024)
Bicarbonate ion-containing solutions such as seawater, natural brines, bovine serum and other mineralizing fluids have been found to contain hyperalkaline droplets of a separate, liquid condensed phase (LCP), that have higher concentrations of bicarbonate ion (HCO3 -) relative to the bulk solution in which they reside. The existence and unique composition of the LCP droplets have been characterized by nanoparticle tracking analysis, nuclear magnetic resonance spectroscopy, fourier transform infrared spectroscopy, dissolved inorganic carbon analysis and refractive index measurements. Carbon dioxide can be brought into solution through an aqueous reaction to form LCP droplets that can then be separated by established industrial membrane processes as a means of concentrating HCO3 -. Reaction of calcium with the LCP droplets results in calcium carbonate precipitation and mineral formation. The LCP phenomenon may bear on native mineralization reactions and has the potential to change fundamental approaches to carbon capture, sequestration and utilization.